Sweat, Tears, And Gold In Political Football - Fahruddiana, Yosphia (PERFECT EDUCATION FAIRY, 2023)
Football is a separate form of entertainment for the community, many think that the atmosphere without football sometimes becomes boring. Basically, football represents love where everyone really wants to see their idol players, football clubs and some styles of football. Many people make football as a source of income. However, there are still many political elites who use it as a political arena to enhance the reputation of individuals or groups. Such a model justifies the existence of political actors in football, so that football matches are sometimes like matches between factions or groups that politicize each other.